2017
DOI: 10.1051/0004-6361/201730911
|View full text |Cite
|
Sign up to set email alerts
|

Correlated uncertainties in Monte Carlo reaction rate calculations

Abstract: Context. Monte Carlo methods have enabled nuclear reaction rates from uncertain inputs to be presented in a statistically meaningful manner. However, these uncertainties are currently computed assuming no correlations between the physical quantities that enter those calculations. This is not always an appropriate assumption. Astrophysically important reactions are often dominated by resonances, whose properties are normalized to a well-known reference resonance. This insight provides a basis from which to deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(78 citation statements)
references
References 45 publications
6
71
1
Order By: Relevance
“…However, the energy resolution of these experiments is insufficient to resolve some of the states observed by Moss [6]. Rather, the discernment that additional states are present comes from the differential cross sections and comparisons to other experimental studies of 26 Mg. The 22 Ne( 6 Li,d) 26 Mg reaction has been measured at a number of different beam energies [10,[12][13][14]. This reaction should preferentially populate natural-parity isoscalar states with large α-particle reduced widths, i.e.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…However, the energy resolution of these experiments is insufficient to resolve some of the states observed by Moss [6]. Rather, the discernment that additional states are present comes from the differential cross sections and comparisons to other experimental studies of 26 Mg. The 22 Ne( 6 Li,d) 26 Mg reaction has been measured at a number of different beam energies [10,[12][13][14]. This reaction should preferentially populate natural-parity isoscalar states with large α-particle reduced widths, i.e.…”
mentioning
confidence: 97%
“…In the absence of existing direct measurements at lower temperatures, the knowledge of the properties of resonances in 26 Mg may be used to better-constrain the 22 Ne+α reaction rates. To this end, a number of experimental studies have been performed to probe the properties of levels in 26 Mg. A brief summary of these experi-mental studies is given so that comparisons to the states observed in the present experiment may be made later. The 26 Mg(p, p ) 26 Mg reaction has been measured at a low proton energy [6].…”
mentioning
confidence: 99%
See 3 more Smart Citations